PENGARUH SUHU AIR PENCUCIAN AMBING DAN TEAT DIPPING TERHADAP JUMLAH PRODUKSI, KUALITAS DAN JUMLAH SEL SOMATIK SUSU PADA SAPI PERANAKAN FRIESIAN HOLSTEIN - HAPPY APRILLIA MAHARDIKA (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This study aimed to investigate the effect of teat dipping on the number of microorganisms based on reductase test and somatic cell, as well as determine the effect udder wash water temperature (temperature of 19-22 °C and 37 °C) on the quality of milk components and quantity of milk production in cows PFH located in KOP SAE Pujon. Sixteen PFH lactation cows were used to test the milk quality with 4 treatments: P0 (temperature 19-22°C, without teat dipping), P1 (temperature 19-22°C with teat dipping after milking), P2 (temperature 37°C with teat dipping after milking) and P3 (temperature 37°C with teat dipping before and after milking). The quality of the milk consists of protein, fat, SNF, solid, density and lactose were analyzed by Lactoscan, microbial test using reductase test, a test of counting the number of somatic cells by the method of breeds, and the amount of production was measured in the morning and afternoon. The results indicated the teat dipping able to increase the time up to 7.3 hours reductase and decrease the number of somatic cell. Water temperature 37°C affected the milk production, but no effect to the milk quality. (Key word: Teat dipping, Milk quality, Dairy cows)